More Than Just Words: Media Literacy and The Development of EFL Writing Class - Nurdianingsih, Fitri; Ghufron, M. Ali; Rohmah, Ima Isnaini Taufiqur; Izzatisselim, Zilvia Nur (IKIP Siliwangi, 2025)
The study concentrated on the opinions and experiences of second-year students enrolled in a writing course that emphasizes media literacy. A case study design is appropriate for this research as it allows for an in-depth exploration of the effects of media literacy-based activities on EFL writing skills within a specific context. Questionnaires on media attitudes and how it affects their writing skills were used to collect data. According to the findings, most students thought that the media literacy exercises improved their ability to think critically, comprehend media messages, and communicate effectively in English. The present study thus underscores the need to embed media literacy into the EFL curriculum to enhance critical thinking among learners and to improve their writing competence. Further research is welcome to help refine these pedagogical strategies and resolve contextual challenges for the best learning outcomes.